The Effects of Methylphenidate on Cognitive Control in Active Methamphetamine Dependence Using Functional Magnetic Resonance Imaging - Jan, Reem K.; Lin, Joanne C.; McLaren, Donald G.; Kirk, Ian J.; Kydd, Rob R.; Russell, Bruce R. (Frontiers in Psychiatry, 2014)
Methamphetamine (MA) dependence is associated with cognitive deficits. Methylphenidate (MPH) has been shown to improve inhibitory control in healthy and cocaine-dependent subjects. This study aimed to understand the neurophysiological effects before and after acute MPH administration in active MA-dependent and control subjects. Fifteen MA-dependent and 18 control subjects aged 18-46 years were scanned using functional magnetic resonance imaging before and after either a single oral dose of MPH (18mg) or placebo while performing a colour-word Stroop task. Baseline accuracy was lower (p=0.026) and response time (RT) was longer (p< 0.0001) for the incongruent compared to congruent condition, demonstrating the task probed cognitive control. Increased activation of the dorsolateral prefrontal cortex (DLPFC) and parietal cortex during the incongruent and Stroop effect conditions, respectively was observed in MA-dependent compared to control subjects (p< 0.05), suggesting the need to recruit neural resources within these regions for conflict resolution. Post- compared to pre-MPH treatment, increased RT and DLPFC activation for the Stroop effect were observed in MA-dependent subjects (p< 0.05). In comparison to MPH-treated controls and placebo-treated MA-dependent subjects, MPH-treated MA-dependent subjects showed decreased activation of parietal and occipital regions during the incongruent and Stroop effect conditions (p< 0.05). These findings suggest that in MA-dependent subjects, MPH facilitated increased recruitment of the DLPFC for Stroop conflict resolution, and a decreased need for recruitment of neural resources in parietal and occipital regions compared to the other groups, while maintaining a comparable level of task performance to that achieved pre-drug administration. Due to the small sample size, the results from this study are preliminary; however, they inform us about the effects of MPH on the neural correlates of cognitive control in active MA-dependent subjects